Evaluation of Histamine in Canned Tuna Fish Post Market Samples in Iran Using ELISA - Hosseini , H.; Dolatabadi, R.; Shekarchi, M.; Keshavarz, A.; Eskandari, S.; Pirali-Hamedani, M. (Asian Journal of Chemistry, 2010)
In the present study, histamine contents of 88 canned tuna fish products from several part of Iran during 2006-2007 were analyzed by using ELISA method. The results showed that 44 % of samples had higher histamine contents than FDA caution level (> 50 ppm). Furthermore the samples from the producers of southern provinces of Iran contained higher amount of histamine than the other in northern parts. The present study also revealed that the histamine amounts depend on production date and increase by closing to expiration date of samples. The results suggested that hygienic quality of canned tuna should be improved by implementing more strict time/temperature controls during commercial processing (cold chain supply).